2013
DOI: 10.1038/ncomms3388
|View full text |Cite
|
Sign up to set email alerts
|

HuR and miR-1192 regulate myogenesis by modulating the translation of HMGB1 mRNA

Abstract: Upon muscle injury the high mobility group box 1 (HMGB1) protein is up-regulated and secreted to initiate reparative responses. Here we show that HMGB1 controls myogenesis both in vitro and in vivo, during development and after adult muscle injury. HMGB1 expression in muscle cells is regulated at the translational level: the miRNA miR-1192 inhibits HMGB1 translation and the RNA-binding protein HuR promotes it. HuR binds to a cis-element, HuRBS, located in the 3′UTR of the HMGB1 transcript, and at the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 66 publications
4
70
0
1
Order By: Relevance
“…For example, HuR inhibits miR-331-3p-mediated repression of ERBB2 expression (45) and miR-494-mediated repression of NCL expression (35). Also, HuR competes with miR-195 to regulate STIM1 mRNA (39) and suppresses miR-1192 to modulate HMGB1 mRNA (46). Although the specific mechanisms whereby HuR and miRNAs compete to regulate joint target mRNAs are not well understood, it is interesting to note that several competing miRNAs have binding sites near the HuR sites (47,48), suggesting that HuR and miRNAs may compete via steric hindrance or local conformational changes of the mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HuR inhibits miR-331-3p-mediated repression of ERBB2 expression (45) and miR-494-mediated repression of NCL expression (35). Also, HuR competes with miR-195 to regulate STIM1 mRNA (39) and suppresses miR-1192 to modulate HMGB1 mRNA (46). Although the specific mechanisms whereby HuR and miRNAs compete to regulate joint target mRNAs are not well understood, it is interesting to note that several competing miRNAs have binding sites near the HuR sites (47,48), suggesting that HuR and miRNAs may compete via steric hindrance or local conformational changes of the mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the expression of HMGB1 is reported to be regulated at a translational level via miR-1192 and HuR in muscle cells upon injury. 44 HMGB1 can signal through the receptor RAGE, TLR2, and TLR4. 26 We previously reported that IA LPS increased TLR2 and TLR4 mRNA expression in the chorioamnion of preterm fetal sheep, 45 similar to women with chorioamnionitis.…”
Section: Discussionmentioning
confidence: 99%
“…High mobility group box 1 (HMGB1), another ligand for RAGE, is a nuclear DNA‐binding protein that can be actively secreted or passively released upon necrotic cell death (but not upon apoptosis) and exert proinflammatory effects by triggering myeloid cells to secrete substantial amounts of TNF‐ α , IL‐1 β , IL‐6, IL‐8, macrophage inflammatory protein (MIP)‐1 α , MIP‐1 β 303, 304, 305. HMGB1 is expressed and released by human skeletal muscle cells upon muscle injury and via binding to RAGE expressed on the surface of myoblasts faciliates myogenesis and muscle regeneration 306, 307…”
Section: Interrelationship Between Inflammation Cell Stress and Myodmentioning
confidence: 99%